Hepatitis C virus in Vietnam: high prevalence of infection in dialysis and multi-transfused patients involving diverse and novel virus variants. - Linda Dunford (Public Library of Science (PLoS), 2012)
Hepatitis C virus (HCV) is a genetically diverse pathogen infecting approximately 2-3% of the world's population. Herein, we describe results of a large, multicentre serological and molecular epidemiological study cataloguing the prevalence and genetic diversity of HCV in five regions of Vietnam; Ha Noi, Hai Phong, Da Nang, Khanh Hoa and Can Tho. Individuals (n=8654) with varying risk factors for infection were analysed for the presence of HCV Ab/Ag and, in a subset of positive specimens, for HCV RNA levels (n=475) and genotype (n=282). In lower risk individuals, including voluntary blood donors, military recruits and pregnant women, the prevalence of infection was 0.5% (n=26/5250). Prevalence rates were significantly higher (p<0.001) in intravenous drug users (IDUs; 55.6%, n=556/1000), dialysis patients (26.6%, n=153/575) commercial sex workers (CSWs; 8.7%, n=87/1000), and recipients of multiple blood transfusions (6.0%, n=32/529). The prevalence of HCV in dialysis patients varied but remained high in all regions (11-43%) and was associated with the receipt of blood transfusions [OR: 2.08 (1.85-2.34), p=0.001], time from first transfusion [OR: 1.07 (1.01-1.13), p=0.023], duration of dialysis [OR: 1.31 (1.19-1.43), p<0.001] and male gender [OR: 1.60 (1.06-2.41), p=0.026]. Phylogenetic analysis revealed high genetic diversity, particularly amongst dialysis and multi-transfused patients, identifying subtypes 1a (33%), 1b (27%), 2a (0.4%), 3a (0.7%), 3b (1.1%), 6a (18.8%), 6e (6.0%), 6h (4.6%), 6l (6.4%) and 2 clusters of novel genotype 6 variants (2.1%). HCV genotype 1 predominated in Vietnam (60%, n=169/282) but the proportion of infections attributable to genotype 1 varied between regions and risk groups and, in the Southern part of Vietnam, genotype 6 viruses dominated in dialysis and multi-transfused patients (73.9%). This study confirms a high prevalence of HCV infection in Vietnamese IDUs and, notably, reveals high levels of HCV infection associated with dialysis and blood transfusion.